Significance of single-nucleotide variants of anorexigenic hormone genes in childhood obesity - A.O. Nikulina (Medičnì Perspektivi, 2024)
Obesity-induced dysregulation of hypothalamic neurons is not completely eliminated by restoring body weight, therefore the most urgent task of modern precision medicine is to predict the trajectory of development of metabolic disorders associated with obesity in children. The aim of the study was to determine the level of association of single-nucleotide variants of genes that determine eating behavior – Neuronal growth regulator 1, Fat mass and obesity associated gene, Glucagon-like peptide-1 receptor, ghrelin, leptin receptor, cholecystokinin, in the development of metabolically unhealthy obesity. 252 obese children aged 6-18 years were examined. The main group (n=152) consisted of children with metabolically unhealthy obesity (MUO) according to Identification and prevention of Dietary- and Lifestyle-induced Health Effects in Children and Infants 2014 criteria. The control group (n=100) consisted of children with metabolically healthy obesity (MHO). All children underwent a general clinical, immunobiochemical examination at the Synevo laboratory (Ukraine). Whole-genome sequencing (CeGat, Germany) was performed in 31 children of the primary and 21 children of the control group. Static analysis: variance analysis ANOVA, method of estimating data dispersion, ROC-analysis, method of testing statistical hypotheses. The level of single nucleotide variants association of anorexigenic hormone genes with MUO that exceeded the threshold accepted by 75% of the available data was, respectively, in ascending order: leptin receptor (LEPR) rs1137101 (40.38%), Glucagon-like peptide-1 receptor (GLP1R) rs1126476 (40.38%), GLP1R rs2235868 (42.31%), GLP1R rs1042044 (42.31%), LEPR rs3790435 (48.08%), cholecystokinin (CCK) rs754635 (50%), LEPR rs2186248 (55.76%), GLP1R rs6918287 (55.76%). Genotypes of the GLP1R gene, such as CC rs10305421 determine insulin resistance (F=5.6); GA/AA rs3765468 – meta-inflammation (F=5.8); AA rs6918287 – basal hyperglycemia (F=6.3) and triglyceridemia (F=51.3), p<0.05. Single-nucleotide variants of the gene GLP1R rs6918287, LEPR rs2186248, CCK rs754635 of the anorexic hormones that control eating behavior are highly associated with the presence of metabolically unhealthy obesity in children.